Controlling emotions—nurses' lived experiences caring for patients in forensic psychiatry. Issue 1 (1st January 2019) - Hammarström, Lars; Häggström, Marie; Devik, Siri Andreassen; Hellzen, Ove
ABSTRACT: Purpose : Nurses working in forensic psychiatry often encounter offenders who have a severe mental illness, which may cause ethical challenges and influence nurses' daily work. This study was conducted to illuminate the meaning of nurses' lived experiences of encounters with patients with mental illnesses in forensic inpatient care. Methods : This qualitative study employed narrative interviews with 13 nurses. Interviews were audiotaped and transcribed verbatim and analysed following a phenomenological-hermeneutic approach. Results : Four key themes were revealed: "Being frustrated" (subthemes included "Fighting resignation" and "Being disappointed"), "Protecting oneself" (subthemes included "To shy away, " "Being on your guard, " and "Being disclosed"), "Being open-minded" (subthemes included "Being confirmed, " "Developing trust, " and "Developing compassion"), and "Striving for control" (subthemes included "Sensing mutual vulnerability" and "Regulating oneself"). Further, working in forensic psychiatry challenged nurses' identity as healthcare professionals because of being in a stressful context. Conclusions : Dealing with aggressive patients with severe mental illnesses threatens nurses' professional identity. Nurses must attempt to empathize with patients' experiences and respond accordingly. Utilizing strategies rooted in compassion such as self-reflection, emotional regulation, and distancing themselves when necessary may enable nurses to more effectively respond to patients' needs.